2022
DOI: 10.3389/fped.2022.720611
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children With Kaposiform Hemangioendothelioma

Abstract: Background and ObjectiveKaposiform hemangioendothelioma (KHE) is a rare, aggressive and borderline vascular tumor mainly occurring in infants and children. The aim of this study was to determine the health-related quality of life (HRQOL) in children with KHE.MeasuresA total of 91 children with KHE participated in this cross-sectional study. The HRQOL was assessed by the age-specific Pediatric Quality of Life Inventory Version 4.0 (PedsQL™ 4.0) Infant Scales, Family Information Form (FIF), Family Impact Module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[2][3][4][5] Clinically, the treatment regimen for KHE is selected based on lesion size, depth, presence of KMP, functional impairment or organ compromise, and treatment side effect profile. [6][7][8][9] Due to the complexity of treatment management as well as the need for risk stratification and differentiation from other vascular anomalies, patients with KHE are often referred to vascular anomaly specialists. 10 Previously, vincristine and/or corticosteroids have been recommended by consensus treatment guidelines as the first-line treatment for KHE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Clinically, the treatment regimen for KHE is selected based on lesion size, depth, presence of KMP, functional impairment or organ compromise, and treatment side effect profile. [6][7][8][9] Due to the complexity of treatment management as well as the need for risk stratification and differentiation from other vascular anomalies, patients with KHE are often referred to vascular anomaly specialists. 10 Previously, vincristine and/or corticosteroids have been recommended by consensus treatment guidelines as the first-line treatment for KHE.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 42% to 71% of KHE patients may suffer from life‐threatening thrombocytopenia, hypofibrinogenemia and consumptive coagulopathy, known as the Kasabach‐Merritt phenomenon (KMP) 2‐5 . Clinically, the treatment regimen for KHE is selected based on lesion size, depth, presence of KMP, functional impairment or organ compromise, and treatment side effect profile 6‐9 . Due to the complexity of treatment management as well as the need for risk stratification and differentiation from other vascular anomalies, patients with KHE are often referred to vascular anomaly specialists 10 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 10 In addition, KMP can affect the health-related quality of life of patients of all ages. 11 Meanwhile, recent research has shown that KMP patients require a longer duration of sirolimus treatment and have a greater rebound rate and more disease sequelae than KHE patients. 12 Given the poor prognosis of the condition and sequelae, KHE patients with KMP tend to require more aggressive management in clinical practice than KHE patients without KMP.…”
Section: Introductionmentioning
confidence: 99%
“…Growth or expansion of VAs can lead to clinical problems, such as disfigurement, bleeding, recurrent infection, chronic pain, thrombocytopenia, consumptive coagulopathy, organ dysfunction, and death [ 2 5 ]. Patients with complicated VAs may suffer from progressive clinical symptoms with decreased quality of life [ 6 ]. Because of the broad spectrum and insufficient treatment regimens, the management of complicated VAs is complex and usually needs a multidisciplinary team with a combination of surgical, interventional (e.g., embolization), and medical treatments [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%